Economic developments in countries of Eastern Europe - Joint Economic Committee (Washington : U.S. Government Printing Office, 1970)
This volume is intended as a benchmark volume. In it, a group of economic specialists evaluate the economies of Eastern Europe against their twenty year record and future prospects.
At head of title: 91st Congress, 2d session. Joint committee print.
A compendium of papers submitted to the Subcommittee on Foreign Economic Policy of the Joint Economic Committee, Congress of the United States.
Includes bibliographical references.
ne 19/06/2018
Loans
Keywords: Economics; Europe, Eastern